2009
DOI: 10.1007/s11033-009-9569-4
|View full text |Cite
|
Sign up to set email alerts
|

pcDNA3.1(−)-mediated ribozyme targeting of HER-2 suppresses breast cancer tumor growth

Abstract: The HER-2 proto-oncogene (also called c-erbB-2/neu) encodes the protein, p185, which is closely related to the growth and metastasis of adenocarcinoma, and is overexpressed in 25-30% of human breast cancers. In this study, we attempt to reverse the malignant phenotype of the breast cancer cell line, MCF-7, using a HER-2-specific hammerhead ribozyme. Two anti-HER-2 hammerhead ribozymes, RZ1 and RZ2, were synthesized, inserted separately into the nonviral eukaryotic expression vector, pcDNA3.1(-), and transfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…ER0051) and ligated by T4 ligase. 18 , 19 The product was then transformed in TOP10 cells by heat shock method and cultured on an ampicillin plate overnight at 37°C overnight. A single transformed colony was cultured in LB media to isolate plasmid by using GeneJET plasmid miniprep kit (Catalog number K0502).…”
Section: Methodsmentioning
confidence: 99%
“…ER0051) and ligated by T4 ligase. 18 , 19 The product was then transformed in TOP10 cells by heat shock method and cultured on an ampicillin plate overnight at 37°C overnight. A single transformed colony was cultured in LB media to isolate plasmid by using GeneJET plasmid miniprep kit (Catalog number K0502).…”
Section: Methodsmentioning
confidence: 99%
“…Two anti-HER-2 ribozymes that specifically target HER-2 mRNA were synthesized and separately assembled in nonviral eukaryotic expression vector. The engineered nanovectors were subsequently used to transfect malignant breast cancer cell lines MCF-7 [78]. The study demonstrated a remarkable downregulation of HER-2 mRNA and concomitantly p185 protein in ribozymes transfected MCF-7 cell lines in addition to upregulation of oncosuppressor gene p53 [78].…”
Section: Functional Nucleic Acids As Biopolymersmentioning
confidence: 97%
“…The engineered nanovectors were subsequently used to transfect malignant breast cancer cell lines MCF-7 [78]. The study demonstrated a remarkable downregulation of HER-2 mRNA and concomitantly p185 protein in ribozymes transfected MCF-7 cell lines in addition to upregulation of oncosuppressor gene p53 [78]. The ability of RNA to fold into 3D structures with pockets and cavities is a strong indication to its potential as binding ligands [79].…”
Section: Functional Nucleic Acids As Biopolymersmentioning
confidence: 99%
“…Ribozymes can specifically cleave target RNA and have been effectively used in gene therapy for cancer and other diseases (Win and Smolke 2008;Culler et al 2010;Mulhbacher et al 2010). For example, a hammerhead ribozyme targeting the human epidermal growth factor receptor HER-2 reversed the malignant phenotype of breast cancer cells (He et al 2010). Metabolite-binding riboswitches also represent a novel solution to sensing and studying metabolic disease.…”
Section: Translational Regulationmentioning
confidence: 99%